Textbook Evaluation from the Perspective of Developing Pronunciation in Primary Learners - Divišovský, Petr (Univerzita Pardubice, 2020)
This bachelor thesis deals with the evaluation of one selected textbook from the perspective of developing pronunciation in primary learners. The theoretical part firstly introduces major phonological terms which are later used throughout the whole thesis. After that it introduces the target group, that is the primary learners with a theory of how to teach and learn pronunciation which later serves for creating criteria for the practical part in which the textbooks are analysed by the criteria in four stages - firstly, the activities developing individual sounds from the perspective of knowledge dimension and cognitive process dimension, then activities developing intonation and word stress. The last stage covers whether the textbook leads the learners towards the expected outputs stated in RVP and CEFR Companion Volume..
Hodnocení učebnic angličtiny: Zaměření na výslovnost
Keywords: výslovnost; aktivity pro rozvoj výslovnosti; suprasegmentální prostředky; srozumitelnost; učebnice; hodnocení; kritéria; pronunciation; pronunciation activities; suprasegmental features; intelligibility; textbook; evaluation; criteria